A group for white women with black children - Rhule, Clare (Groupwork, 2020)
This group was set up by two workers, a white woman and a black woman, to look « issues of racism and anti-racist parenting. Tim group, which ran for 18 months, Provided a forum for women to share their experiences of having a relationship with a black man and bringing up a black child in a white ethnocentric society. Using various groupwork methods, the workers attempted to raise group members’ awareness of both personal and institutional racism and how they affect both black and white people. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are searchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication.